Structural and dynamic changes in mixed forests of beech and fir on Mt. Goč - Snežana Obradović; Damjan Pantić; Milan Medarević; Biljana Šljukić; Biljana Pešić (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The primary goal of this research was to analyze the structural, production and dynamic changes of the forests of beech and fir in permanent sample plots of Mt. Goč, excluded from regular management for a period of 35 years (1977–2011). The established principles of spontaneous development and selfregulatory processes could have implications on the regular management in these forests located in the area of Mt. Goč and other areas.